Study of invertase biosynthesis during fermentation by strain Aspergillus niger L-4 - Kulaipbekova, А.А.; Katasheva, A.Ch.; Znenisova, A.Zh.; Baibekova, A.U. (Fundamental and Experimental Biology, 2022)
The use of enzymes or microorganisms in food products is a long-standing process. With the development of technology, new enzymes have been developed with a wide range of uses and specifics, and a new field of applications is still being studied. Microorganisms such as bacteria, yeast, and micromycetes and their enzymes are widely used in food preparations to improve taste and texture; they provide economic benefits for industry. The production of microbial enzymes has such advantages as simplicity, cost-effectiveness, and stability. The study of enzymes is of particular interest since enzyme preparations are widely used in various industries: agriculture, medicine, and genetic engineering. Enzymes of microbial origin as biocatalysts accelerate the process at a rate and order of magnitude higher than inorganic catalysts. This article examines the ability of the strain of micromycete Aspergillus niger L-4 — producer of citric acid to synthesize the enzyme invertase when cultured on a nutrient medium consisting of hydrolysate of rye grain grinding. Based on the study of invertase biosynthesis, it was found that the most preferable and cost-effective option for hydrolysis of rye grain grinding is the use of dosages of enzyme preparations: celloviridin — 4 units/g, amylosubtilin — 2 units/g and β-glucanase — 3 ed/g. Under these conditions, the content of soluble carbohydrates was (%): DE — 43.7±3.4, glucose — 16.8±1.3, maltose — 76.8±3.8, dextrins — 6.4±0.5 and the amount of acid is higher than in the variant without beta-glucanase.